Scary stories for young foxes - Heidicker, Christian McKay; Playaway Digital Audio; Findaway World, LLC; Recorded Books, Inc. (Solon, OH : Findaway World, LLC, 2020)
A collection of eight interconnected stories that follows a group of fox kits as they fight to survive in an unforgiving wilderness.
Miss Vix -- Six sisters -- House of trix -- Creeeaaak THUMP! Creeeaaak THUMP! -- Slither out of darkness -- Lilac kingdom -- Paw -- Snow ghost.
Originally released on compact disc by Recorded Books.
Accompanying material may vary.
Title from Playaway unit label.
"Playaway Kids. Bold. Bright. Audiobooks."--Container insert.
Read by the author.
Playaway Digital Audio.
Keywords: Foxes -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Survival -- Juvenile fiction; Foxes -- Juvenile sound recordings; Animals -- Infancy -- Juvenile sound recordings; Survival -- Juvenile sound recordings; Storytelling -- Juvenile sound recordings; Playaway (Preloaded audio player); Adventure and adventurers -- Fiction; Storytelling -- Fiction; Horror stories; Action and adventure fiction; Animal fiction; Audiobooks; Children's audiobooks; Horror fiction; Juvenile works; Sound recordings; Animal fiction; Action and adventure fiction; Horror fiction; Children's audiobooks; Sound recordings; Children's sound recordings